Bacillus methylotrophicus WM‐1 enhances the immunity of grass carp against Aeromonas hydrophila. (2nd February 2022) - Li, Yanhong; Luo, Lijun; Yang, Qinglin; Zhang, Wenjin; Tang, Xiaoqi; Yu, Xiaobo; Wu, Zhengli
Abstract: Aeromonas hydrophila is a common pathogen and causes huge economic losses in aquaculture; to date, we still have no efficient methods to control fish diseases caused by A . hydrophila . Our previous research found that a strain of Bacillus   methylotrophicus WM‐1 could effectively inhibit A . hydrophila KS02. In the current study, the safety of WM‐1 and its protective effects against A . hydrophila in the aquaculture system were examined. Grass carp were selected and fed with WM‐1 supplemented feed (0, 10 3, 10 5 and 10 7 CFU/g feed, as CG, LG, MG and HG) for a period of 90 days. On day 30, grass carp were challenged with KS02 (WM‐1+KS02 group) or saline (WM‐1 group) as control. The growth performance and enzyme activities were measured; blood routine tests were conducted on day 90. In the WM‐1 group, AKP activity in the serum was significantly reduced and SOD activity in the liver was significantly enhanced by WM‐1 supplemented feed, while other monitored indices had no significant changes. In the WM‐1+KS02 group, GPT activity in the serum and SOD activity in the liver were significantly enhanced, while AKP activity in the serum had no significant change except for the MG group. Survival rates of grass carp were advanced by WM‐1 supplemented feed, reaching 70% after challenge with KS02. Overall, WM‐1 could maintain the homeostasis of grass carp and protected them against A . hydrophila infection efficiently, which indicated WM‐1 would be a probiotic candidate for use in aquaculture.